The Influence Of Motivation, Competence And Training On The Performance Of Employees At Pt Penascop Maritime Of Indonesia In East Waringin City Regency - M. Thamrin Noor (International Journal of Science, Technology & Management, 2022)
The title of this research is the Influence of Motivation and Competence of Training on Employee Performance at PT. Penascop Maritime of Indonesia in East Kotawaringin Regency. This research using the Slovin Formula with the techniques Probability Sampling; Simple Random Sampling with a population of 90 people and a sample of 73 people. And the data in the test by using descriptive analysis, multiple linear regression analysis, correlation coefficient analysis, and the analysis of the coefficient of determination. The results of t-test for the variable of Motivation (X1) that tcount>ttable (2,866 > 1,99495) and the level of sig of 0.006 < 0.05, the Variable Competence (X2) with the value of tcount<ttable (0,498 < 1,99495) with the level of sig 0,498 > 0.05 and Variable Training (X3) with a value of tcount<ttable (0,228 < 1,99495) with the level of sig 0,228 > 0,05 Based on test-f ( simultaneous ) shows that the influence together of all the independent Variables of motivation (X1), competence (X2) and training (X3) to the variable depanden the employee’s performance (Y) showed significant results. It is shown from the Value of fcount>ftable (63,841 > 3,13) with a significant level of 0,000 < 0,05. The results of the analysis of the correlation coefficient ®of 0,857 means the relationship between the variables of motivation, competence and training on employee performance or R-Square (R2) with a magnitude of R Square 0,735 or of 73.5% means that the variables of motivation, competence and training affect the performance of employees of 73.5%. While the rest of 26.5% for the variable employee performance is influenced by other variables such as leadership style, work load and so forth. Based on the test results of the multiple linear regression equation was obtained: Y = 2,135 + 0,280 (X1) + 0,173 (X2) + 0,416 (X3), meaning that the score / constant value (ɑ) shows if there is no increase in the variables of motivation, competence and training, the value of the performance of the employees is 2,135 and any addition of a score/the value of the variable motivation give rise equal to 0.280 on the performance of employees with terms X2 fixed, as well as any addition of a score/the value of the variable competence to give rise to the same by 0,173 on the performance of employees with terms of X1 fixed, and if any addition of a score/the value of variable training gives the same increase of 0,416 on the performance of employees with terms X3 fixed.